Major depressive disorder - Marx, Wolfgang; Penninx, Brenda W. J. H.; Solmi, Marco; Furukawa, Toshi A.; Firth, Joseph; Carvalho, Andre F.; Berk, Michael (Nature reviews. Disease primers, 2023)
Major depressive disorder (MDD) is characterized by persistent depressed mood, loss of interest or pleasure in previously enjoyable activities, recurrent thoughts of death, and physical and cognitive symptoms. People with MDD can have reduced quality of life owing to the disorder itself as well as related medical comorbidities, social factors, and impaired functional outcomes. MDD is a complex disorder that cannot be fully explained by any one single established biological or environmental pathway. Instead, MDD seems to be caused by a combination of genetic, environmental, psychological and biological factors. Treatment for MDD commonly involves pharmacological therapy with antidepressant medications, psychotherapy or a combination of both. In people with severe and/or treatment-resistant MDD, other biological therapies, such as electroconvulsive therapy, may also be offered. This Primer summarizes the epidemiology, mechanisms, diagnosis and treatment of major depressive disorder (MDD). This Primer also reviews how this disorder affects patient quality of life, and provides an overview of future research.